Midwives’ Experiences in Providing Maternal Health Services during the COVID-19 Pandemic: A Qualitative Study at Sedayu I Primary Health Centre - Rodliah Rosyad, Shelly; Astuti, Andari Wuri; Hidayat, Asri; Astuti, Dhesi Ari (Gaster, 2025)
Background During the COVID-19 pandemic, midwives experienced increased physical and emotional fatigue, elevating their risk of burnout and potentially impacting the quality of maternal healthcare services. Objective This study aimed to explore midwives’ lived experiences in delivering antenatal and childbirth care during the COVID-19 pandemic. Methods A qualitative study was conducted using a phenomenological approach. Seven midwives from Sedayu I Primary Health Centre were selected through purposive sampling. One-on-one in-depth interviews were carried out using an interview guide, audio recording, and field notes. Data were analyzed using Colaizzi’s thematic analysis method. Ethical approval was obtained from the Research Ethics Committee of Universitas ‘Aisyiyah Yogyakarta. Results Five major themes emerged: (1) psychological conditions, including anxiety and preparedness; (2) service changes during the pandemic, encompassing antenatal care, childbirth, and adaptation to new health protocols; (3) constraints, such as challenges in PPE usage and referral systems; (4) internal and external support systems; and (5) needs and expectations, including human resource support and access to updated information. Conclusion This study offers valuable insights into the challenges and adaptations experienced by midwives during the COVID-19 pandemic. Findings highlight the importance of integrating midwives’ experiences into healthcare system planning and policy formulation for future pandemic preparedness and maternal service resilience.